THE IMPACT OF DIGITALIZATION ON THE INTERNATIONAL COMPETITIVENESS OF KAZAKHSTAN’S ECONOMY - Amankeldi V.K. (Research Reviews, 2026)
This article examines the impact of digitalization on the international competitiveness of Kazakhstan’s economy. The adoption of digital technologies (ICT infrastructure, e-government, electronic commerce) significantly increases productivity, fosters innovation, and improves the business climate. Kazakhstan has made moderate progress: it ranks 55th in the Global Competitiveness Index (GCI 2019) and 25th in Doing Business 2020, reflecting gains in online services and regulatory efficiency. However, its innovation ranking (GII 2023: 81st) and very low R&D intensity (≈0.14% of GDP in 2023) indicate a persistent technological gap. GDP per capita (PPP) grew from $22,484 in 2015 to $38,515 in 2023, showing economic growth but insufficient innovation